2020
DOI: 10.1108/k-07-2019-0499
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of high-speed railway on the industrial pollution emissions in China

Abstract: Purpose The purpose of this paper is to analyse the impact of high-speed railway (HSR) on industrial pollution emissions using the data for 285 prefecture-level cities in China from 2004 to 2016. Design/methodology/approach The research method used in this paper is the multi-period difference-in-differences (DID) model, which is an effective policy effect assessment method. To further address the issue of endogeneity, the DID integrated with the propensity score matching (PSM-DID) approach is employed to eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Some missing data are completed by interpolation method. To alleviate the problem of heteroscedasticity, non-percentage variables are logarithmised (Fan et al, 2020). Descriptive statistics of each variable are reported in Table 2.…”
Section: Data Sources and Processingmentioning
confidence: 99%
“…Some missing data are completed by interpolation method. To alleviate the problem of heteroscedasticity, non-percentage variables are logarithmised (Fan et al, 2020). Descriptive statistics of each variable are reported in Table 2.…”
Section: Data Sources and Processingmentioning
confidence: 99%
“…On the one hand, industrial agglomeration will produce a scale effect, which will reduce its production cost. Then it will be more conducive to technological innovation, which promotes clean production and ultimately helps to promote the efficiency of carbon dioxide emission [18,33,39,40]. On the other hand, high-speed rail construction can enhance the agglomeration advantages of labor and other factors in backward areas.…”
Section: High-speed Rail Construction Manufacturing Agglomeration And...mentioning
confidence: 99%
“…In addition, public infrastructure is regularly treated as the key to promoting economic efficiency by reducing production costs and transaction costs (Chen and Vickerman, 2016;Diao, 2018). The role of rail transit in reducing air pollution (Zheng S. et al, 2019;Guo and Chen, 2019) and improving environmental quality (Fan et al, 2020;Guo et al, 2020) has also been widely confirmed. This raised the question of what impact HSR, which integrates clean, speed, convenience, and safety (Guo et al, 2020), has on the GTFP?…”
Section: Introductionmentioning
confidence: 99%